The important of social and economic aspects in integrated drainage basin management system - Jamaluddin Md Jahi, (Environmental Management Society, Malaysia, 2001)
Drainage basin is an interactive and dynamic complex of open physical system. The system emphasizes on adjustment and relationships between physical form and process and the influence of human being. Although, all development that take places on land is confined to drainage basin, more often than not the importance of social and economic aspects are not considered within or in adjacent drainage basins especially when it only involves project planning and implementation. As such some projects are not cost effective and leave much to be desired. It is imperative that social and economic aspects be identified, inventoried and accounted for in any development project proposal alongside the physic-chemical and biological characteristics. The establishment of drainage basin data-base for a holistic and integrated drainage basin management system can now be done easily with the help of remote sensing data and geographic information system with ground checking, if necessary